2020
DOI: 10.3389/fphar.2020.00457
|View full text |Cite
|
Sign up to set email alerts
|

Terphenyllin Suppresses Orthotopic Pancreatic Tumor Growth and Prevents Metastasis in Mice

Abstract: Pancreatic cancer (PC) is an aggressive and fatal disease with high incidences of metastasis and recurrence. However, there are no effective treatment options for the majority of PC patients, especially for those with locally advanced tumors and metastatic diseases. Therefore, it is urgently needed to develop safe and effective anti-PC therapeutic agents. We have recently identified a novel marine-derived natural product terphenyllin with potent anti-PC activity. The present study was designed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Terphenyllin is a naturally abundant p-terphenyl metabolite isolated from the coral derived fungus Aspergillus candidus that has α-glucosidase inhibitory activity and was shown to inhibit PDAC growth and metastasis in a mouse model by inducing apoptosis through Bax, Bad and Puma [62].…”
Section: α-Glucosidase Inhibitorsmentioning
confidence: 99%
“…Terphenyllin is a naturally abundant p-terphenyl metabolite isolated from the coral derived fungus Aspergillus candidus that has α-glucosidase inhibitory activity and was shown to inhibit PDAC growth and metastasis in a mouse model by inducing apoptosis through Bax, Bad and Puma [62].…”
Section: α-Glucosidase Inhibitorsmentioning
confidence: 99%
“…β-catenin and MDM2) and/or reactivating tumor suppressors (e.g. p53 and Puma) ( Li et al., 2013 ; Qin et al., 2018a ; Wang W. et al., 2018 ; Wang et al., 2020 ; Zhang J. et al., 2020 ). It has also been reported that natural products can enhance the chemosensitivity of cancer cells by suppressing the functions of drug resistance-related proteins ( Feng et al., 2017 ; Dong et al., 2020 ; Yuan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cell viability assay was performed as described previously ( Wang et al, 2020a ; Zhang et al, 2020 ). Briefly, cells were grown in 96-well plates (3 × 10 3 cells/well) for 24 h and incubated with DOX, FU-DOX, or FA-FU-DOX at equivalent concentrations for 72 h. Then, 10 μL of CCK-8 solution (Beyotime, CA) was added to each well.…”
Section: Methodsmentioning
confidence: 99%